Protective Factors, Coping Appraisals, and Social Barriers Predict Mental Health Following Community Violence: A Prospective Test of Social Cognitive Theory. Issue 3 (June 2017) - Smith, Andrew J.; Felix, Erika D.; Benight, Charles C.; Jones, Russell T.
Abstract : This study tested social cognitive theory of posttraumatic adaptation in the context of mass violence, hypothesizing that pre‐event protective factors (general self‐efficacy and perceived social support) would reduce posttraumatic stress symptoms (PTSS) and depression severity through boosting post‐event coping self‐efficacy appraisals (mediator). We qualified hypotheses by predicting that post‐event social support barriers would disrupt (moderate) the health‐promoting indirect effects of pre‐event protective factors. With a prospective longitudinal sample, we employed path models with bootstrapping resampling to test hypotheses. Participants included 70 university students (71.4% female; 40.0% White; 34.3% Asian; 14.3% Hispanic) enrolled during a mass violence event who completed surveys one year pre‐event and 5–6 months post‐event. Results revealed significant large effects in predicting coping self‐efficacy (mastery model, R 2 = .34; enabling model, R 2 = .36), PTSS (mastery model, R 2 = .35; enabling model, R 2 = .41), and depression severity (mastery model, R 2 = .43; enabling model, R 2 = .46). Overall findings supported study hypotheses, showing that at low levels of post‐event social support barriers, pre‐event protective factors reduced distress severity through boosting coping self‐efficacy. However, as post‐event social support barriers increased, the indirect, distress‐reducing effects of pre‐event protective factors were reduced to nonsignificance. Study implications focus on preventative and responsive intervention.